The role of inflammasomes in intestinal inflammation - Srinivasan, N (2014)
Single Nucleotide Polymorphisms (SNPs) in the intracellular pattern recognition receptor gene NLRP3 are associated with susceptibility to Crohn’s disease, a form of inflammatory bowel disease (IBD). Following cell damage or infection, NLRP3 triggers the formation of inflammasomes, a multimolecular protein complex containing NLRP3, ASC and caspase-1, which mediate secretion of IL-1β and IL-18. NLRP3 inflammasome activation in macrophages has been implicated in protection against several pathogens, but whether NLRP3 activation in tissue cells contributes to protective immunity against bacterial pathogens is unknown. We show that upon infection with the attaching/effacing (A/E) intestinal pathogen Citrobacter rodentium, Nlrp3-/- and Asc-/- mice displayed higher bacterial colonization, more weight loss and exacerbated intestinal inflammation. We further show that Nlrp3 inflammasome activation in intestinal epithelial cells (IECs) acts rapidly after infection to limit bacterial replication and penetration, and inhibits the development of inflammatory pathology in the gut. We also show that epithelial Nlrp3-mediated protection is independent of the classical inflammasome cytokines IL-1β and IL-18. Thus an Nlrp3-Asc circuit in IECs regulates early defense against a mucosal pathogen and limits inflammation in the intestine. Nlrp3 inflammasome activation has also been implicated in protection in acute models of experimental colitis, but its role in chronic models of colitis is unknown. We found that Asc signaling is necessary for the development of innate chronic intestinal inflammation driven by Helicobacter hepaticus. Thus while deficient inflammasome signaling in tissue cells increases susceptibility towards enteric pathogens, excessive inflammasome activation can drive chronic intestinal inflammation.